Working Time Reductions at the End of the Career. Do they Prolong the Time Spent in Employment? - Andrea Albanese; Bart Cockx; Yannick Thuy (Center for Economic Studies and ifo Institute (CESifo), 2016)
In this paper we study the effects on the survival rate in employment of a scheme that facilitates gradual retirement through working time reductions. We use information on the entire labour market career and other observables to control for selection and take dynamic treatment assignment into account. We also estimate a competing risks model considering different (possibly selective) pathways to early retirement. We find that participation in the scheme initially prolongs employment, as participants keep accumulating full pension rights. However, as participants become eligible for early retirement subsequently, these larger financial incentives induce them to leave the labour force prematurely. These adverse incentives are stronger for individuals who reduce their working time most. After two (four) years for men (women), the positive effects reverse. The more favourable effect for women is likely a consequence of their lower opportunities to enter early retirement. The gradual retirement scheme fails the cost-benefit test.
Keywords: J14; C22; J18; J22; 330; part-time work; older workers; inverse probability weighting; dynamic selection into treatment; endogenous sampling